Regulations and technology gap in Europe: The role of firm dynamics - Sara Amoroso; Roberto Martino (European Commission, Joint Research Centre (JRC), 2020)
In this paper, we develop a new firm-level measure of distance to the productivity frontier that accounts for international technology spillovers stemming from the use of imported intermediate goods. The trade-weighted technological distance to frontier is matched with sector- and country-level data on regulation and firm dynamics (entry and exit rates) of 16 European countries. Using our measure of trade-adjusted technology gap, we investigate the role of labour, capital, and product market regulatory frameworks in the technology catch-up process, gauging the effect of firms' dynamics in mediating and moderating the impact of regulation on the technology gap. Our study offers a novel perspective and insights to the analysis of the link between framework conditions and technological distance to frontier. While most scholars argue that less regulation always favours productivity growth and the diffusion of technology, our results provide a more nuanced picture. Deregulation is not a one-size-fits-all solution that leads to faster technology diffusion, instead heterogeneity in business dynamism and countries' regulatory structures need to be considered.
Keywords: L16; L50; M21; O33; 330; Innovation diffusion; Framework conditions; Business dynamics; Technological frontier